Exploring the Influence of Chalcogens on Metalloporphyrins: A DFT Study - Beenish Bashir; Andre Z. Clayborne (Molecules)
Metalloporphyrins and porphyrins (MPs) have garnered increasing attention as potential candidates for molecular-based electronic devices and single-atom catalysis. Recent studies have found that electronic structure calculations are important factors in controlling the performance of MPs as building blocks for single-molecule devices. Our study investigates metalloporphyrins with central 3d-metals from Sc to Cu and chalcogen containing anchoring groups such as -SH, -SeH, and -TeH substituted at the meso-position of the porphyrin rings. We carried out Density Function Theory (DFT)-based calculations to determine the ground state geometry, spin multiplicity, spatial distribution of the molecular orbitals, and electronic structure descriptors to gain insights into the reactivity trends and possible impact on factors influencing electron transport properties. The results suggest that the central metal shapes the spin multiplicity, while variations between sulfur, selenium, and tellurium play a role in charge distribution. This study provides insights into how the selection of the central metal and control of spin channels influence the electronic structure and reactivity of metalloporphyrin molecules. The knowledge provided here can play a role in the design of porphyrin-based molecular materials for diverse applications in molecular junctions, catalysis, photovoltaics, and sensing.